The Panoptic Sibyl System and the Dystopia in Gen Urobuchi’s Psycho Pass - Chitra Santy; Liliek Soelistyo (Institute of Research and Community Outreach - Petra Christian University, 2014)
This study aims to prove that Sibyl System is the Panopticon and to analyze the causes of dystopia in Gen Urobuchi’s Psycho Pass. In Psycho Pass, Sibyl System is the governing system which possesses a resemblance to the Panopticon. It implies that Sibyl System may actually be a Panopticon; thus, we want to prove this using the theory of the Panopticon by Michel Foucault. Moreover, Sibyl System shows signs of being the cause of the dystopian society in Psycho Pass even though it was designed to create utopia. To find out more about this, we analyze each characteristic of the dystopian society and trace their causes to Sibyl System’s aspects. Through the analysis, by comparing Sibyl System’s aspects to six of the Panopticon’s aspects, it is found that Sibyl System is indeed a Panopticon, and these panoptic aspects with its loopholes are the causes of the dystopian society. In conclusion, a Panopticon such as Sibyl System, though designed with noble intentions, can have flaws that prove fatal in changing the society into a dystopian one